The Effect of Information Technology Capability On Company Performance Mediated By Organizational Ambidexterity In SME’s In Harau Distric - S, Fadhilah.; Linda, Muthia Roza (Human Resource Management Studies, 2025)
This research analyzes: 1. To determine the influence of Information Technology Capability on performance in UKM in Harau District. 2. To determine the influence of Information Technology Capability on Organizational ambidexterity in UKM in Harau District. 3. To determine the influence of organizational ambidexterity on performance in Harau District UKM. 4. To determine the influence of Information Technology Capability on FirmPerformance mediated by Organizational ambidexterity of Harau District UKM. This research is causal research. The sample for this research is that this research uses 170 samples of SMEs in Harau District that meet the specified criteria. The sampling technique was carried out using total sampling. Data collection used a questionnaire with a Likert scale. The analysis technique uses PLS 4 software. The results of this study show that: 1. There is a positive and significant influence of Technology Information Capability on Organizational Ambidexterity in UKM in Harau District. 2. There is a positive and significant influence of Technology Information Capability on FirmPerformance in SMEs in Harau District. 3. There is a positive and significant influence of Organizational Ambidexerity on FirmPerformance in SMEs in Harau District 4. Organizational Ambidexerity is able to mediate the positive and significant influence of Technology Information Capability on FirmPerformance in SMEs in Harau District